Rationality Reconsidered: Ortega y Gasset and Wittgenstein on Knowledge, Belief, and Practice - Wagner, Astrid; Ariso Salgado, José María (Rationality Reconsidered: Ortega y Gasset and Wittgenstein on Knowledge, Belief, and Practice, 2023)
This volume treats the topic of rationality developing a perspective that integrates elements of philosophy of language, phenomenology, pragmatism, and philosophy of life. The two reference authors, Wittgenstein and Ortega, are contemporaries but come from different philosophical traditions. Wittgenstein's early work was influenced by logical positivism. Later he developed an influential approach to philosophy of language. Ortega was influenced by Neo-Kantianism, perspectivism, life philosophy, and phenomenology. On this basis, he developed an independent approach that has become known as ratiovitalism. Astonishing affinities between their respective reflections on rationality motivated the experiment of bringing the different approaches into a synergetic relation. Both investigate the structures and limits of rationality, emphasize the importance of basic beliefs, and criticize the restriction of rationality concepts to the intellectual sphere. The contributions of the volume focus on: dynamics of belief and knowledge, implicit and explicit knowledge, the concept of “vital reason”, the role of world-pictures and forms of life, questions regarding certainty, ignorance, doubt, and madness, as well as matters of pluralism and relativism.
Keywords: phenomenology; Philosophy of language; pragmatism; ratiovitalism; Scopus(2)